2021
DOI: 10.1186/s13068-021-01962-6
|View full text |Cite
|
Sign up to set email alerts
|

Increasing lipid yield in Yarrowia lipolytica through phosphoketolase and phosphotransacetylase expression in a phosphofructokinase deletion strain

Abstract: Background Lipids are important precursors in the biofuel and oleochemical industries. Yarrowia lipolytica is among the most extensively studied oleaginous microorganisms and has been a focus of metabolic engineering to improve lipid production. Yield improvement, through rewiring of the central carbon metabolism of Y. lipolytica from glucose to the lipid precursor acetyl-CoA, is a key strategy for achieving commercial success in this organism. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 56 publications
0
11
1
Order By: Relevance
“…In contrast, the introduction of phosphoketolase bypass, which has been shown to be largely beneficial for enhancing the production of metabolites downstream of acetyl-CoA in various studies (1518, 20, 21), led to decreased production, yield, and content of beta-carotene in our study. In three studies that have utilized the same set of genes for the phosphoketolase bypass as we did, the authors have observed positive impact on the production of acetate (17) and lipids (15), and no impact on the production of alpha-humulene (19).…”
Section: Resultscontrasting
confidence: 78%
“…In contrast, the introduction of phosphoketolase bypass, which has been shown to be largely beneficial for enhancing the production of metabolites downstream of acetyl-CoA in various studies (1518, 20, 21), led to decreased production, yield, and content of beta-carotene in our study. In three studies that have utilized the same set of genes for the phosphoketolase bypass as we did, the authors have observed positive impact on the production of acetate (17) and lipids (15), and no impact on the production of alpha-humulene (19).…”
Section: Resultscontrasting
confidence: 78%
“…Over the past several years, great progress has been made to improve lipid and lipid-derivatives production by Y. lipolytica [ 48 , 49 , 50 ]. Different strategies have been used for increasing lipid accumulation and recovery from Y. lipolytica [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The knockout of phosphofructokinase (PFK) in Yarrowia lipolytica blocked the metabolic flux of G6P in glycolysis and caused the redox imbalance with excess NADPH production. Then the introduction of the PHK pathway resulted in the accumulation of acetyl-CoA and correction of the redox imbalance by providing a route towards the NADPH-oxidizing lipid synthesis pathway, and a 19% increase in total lipid production was derived in the host strain [ 26 ]. In the TCA cycle, citrate can be catalyzed by ATP:citrate lyase (ACL) to produce acetyl-CoA [ 27 ].…”
Section: Application Of Ccm Optimization In Yeastmentioning
confidence: 99%